ThManager: An Open Source Tool for Creating and Visualizing SKOS - Lacasta, Javier; Nogueras-Iso, Javier; López-Pellicer, Francisco Javier; Muro-Medrano, Pedro Rafail; Zarazaga-Soria, Francisco Javier (Information Technology and Libraries, 2007)
Knowledge organization systems denotes formally represented knowledge that is used within the context of digital libraries to improve data sharing and information retrieval. To increase their use, and to reuse them when possible, it is vital to manage them adequately and to provide them in a standard interchange format. Simple knowledge organization systems (SKOS) seem to be the most promising representation for the type of knowledge models used in digital libraries, but there is a lack of tools that are able to properly manage it. This work presents a tool that fills this gap, facilitating their use in different environments and using SKOS as an interchange format.